The Study of Social and the Economical Factors on Prostitution Phenomena in Shiraz at 2010 - hossein izadi; afrasiab zarghami (توسعه اجتماعی)
The aim of fulfillment of this research is the study of effective and economical factors on prostitution in Shiraz at 2010. This research has fulfilled with measurement method and also descriptive and analytic ways. There are choosing 100 samples from prostitute women for determining sample volume. After collecting information in framework of prostitution questionnaire. Datas have analyzed with spss software and statistic test of linear regression based of descriptive and analytical tables. The findings of (1) table show that among usual and prostitute samples %20 and 49 samples 49 % have found effective greatly civil life factors in prostitution phenomena. The findings of table, (2) among the samples which have usual and ethical deviation, 47 sample %47 and 44 samples 44 % have (understood) found effective greatly the absence of social monitoring in appearance of prostitution phenomena. The table (3) shows that among the samples which have usual and ethical deviations, 79 samples %79 and 58 samples %58 have understood effective greatly the family negative application in appearance of prostitution phenomena. The findings of table (4) show that among the sample which have usual and ethical deviations, 51 samples %51 and 35 samples %35 have understood (found) effective greatly ethical coarseness factors in appearance of the findings of table (5) show that among the samples of usual a prostitute 59 samples %59 and 53 samples %53 have understood effective greatly individual factor in prostitution. There fore, there a meaning ful relations ship among each of 5 variables and prostitute phenomena (p < .05).